Lean and Non-obese Metabolic Dysfunction Associated Steatotic Liver Disease in Diabetics and Gender-wise association in a Low-income country - Malik, Falak Naz; Shabnam Naveed; Syed Masroor Ahmad; Zeeshan Ali; Marium Fatima Waqar (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the prevalence of lean, non-obese and obese metabolic dysfunction-associated steatotic liver disease in diabetics, and to explore gender-wise correlation of lifestyle, hypertension and dyslipidaemia with body mass index categories. Method: The descriptive study was conducted at the Diabetes Clinic of Jinnah Postgraduate Medical Centre, Karachi, from March 1 to August 25, 2023, and comprised adult patients of either gender having fatty liver. Data regarding patients’ demographics, baseline characteristics and history of hypertension, dyslipidemia and duration of diabetes was collected using a predesigned proforma. Data was analysed using SPSS 21. Results: Of the 229 patients with mean age 53.12±9.82 years, 151(65.93%) were females. Overall mean body mass index was 27.41±4.80kg/m2. Triglycerides, low-density lipoprotein, body mass index and waist circumference values were significantly raised in obese patients (p<0.05). Overall, 153(66.8%) patients had obese metabolic dysfunction-associated steatotic liver disease, and, of them, 111(72.5%) were females (p<0.05). Sedentary lifestyle was more prevalent in females than in males (p<0.05). Conclusion: A significant number of diabetics were found to have obese metabolic dysfunction-associated steatotic liver disease, and it was significantly more common among females. Sedentary lifestyle was also significantly more prevalent in female diabetics. Key Words: MASLD, Lean, Non-obese, Diabetics, BMI.